Sex Related Differences in the Risk of Antibody-Mediated Rejection and Subsequent Allograft Vasculopathy Post-Heart Transplantation: A Single-Center Experience. Issue 10 (October 2016) - Grupper, Avishay; Nestorovic, Emilija M.; Daly, Richard C.; Milic, Natasa M.; Joyce, Lyle D.; Stulak, John M.; Joyce, David L.; Edwards, Brooks S.; Pereira, Naveen L.; Kushwaha, Sudhir S.
Abstract : Background: Pregnancies may result in antibodies against HLA, a risk factor for antibody-mediated rejection (AMR) and subsequent cardiac allograft vasculopathy (CAV) after heart transplantation (HTx). The aim of this study was to evaluate sex differences in the incidence of AMR events and subsequent risk of CAV among HTx recipients. Methods: The study comprised 160 patients (51 [32%] women) who underwent HTx in 2008 to 2014. The cumulative effect of AMR events was calculated by AMR score (sum of myocardial biopsy grading divided by number of biopsies taken during 3 years post-HTx). Results: Females had higher levels of anti-HLA I antibodies pre-HTx compared to males which was associated with a history of pregnancies, total number of children and with a higher AMR score at 6 months post-HTx ( P < 0.05). Women demonstrated a significant increase in the total incidence of AMR events (27 vs. 7%, P = 0.001) and in AMR scores at 6, 12, 24 and 36 months post-HTx compared to men ( P < 0.05). There were no differences in cellular rejection between the groups. A history of AMR events was associated with a significantly increased risk of severe CAV onset (hazard ratio, 7.0; 95% confidence interval, 1.5-31.5; P = 0.012). Conclusions: Women are at higher risk for AMR post-HTx which subsequently increases their risk for CAV. Females recipients may benefit from closer surveillance to identify AMR at an earlier stage post-HTx, and targeted immunosuppressive therapy to attenuate the development of CAV.